METHODOLOGICAL PROBLEMS OF MANAGEMENT QUALITY OF EDUCATION (Pedagogy of Higher and Secondary Education, 2004)
The article investigates methodological problems of qualitative characteristics of educational reforms and the ways of their possible solution.